Evaluation of validity of Tanaka-Johnston analysis in Mumbai school children - Chaitali Umesh Hambire; Sunanda Sujan (Wolters Kluwer Medknow Publications, 2015)
Introduction: Estimation of the mesiodistal dimensions of the unerupted canines and premolars in the early mixed dentition is a necessary diagnostic aid in space management. Tanaka-Johnston analysis was developed for North American children. Anthropological study reveals that tooth size varies among different ethnicities. The present study was performed to evaluate the validity of Tanaka-Johnston method of mixed dentition arch analysis in Mumbai school children. Aims: (1) To determine the correlation between the sum of the mesiodistal widths of the permanent mandibular incisors and combined mesiodistal widths of the permanent mandibular and maxillary canines and premolar in Mumbai school children. (2) To examine the applicability of Tanaka-Johnston method of prediction. Materials and Methods: Dental casts of maxillary and mandibular arches of 300 children, 147 boys and 153 girls within the age group of 12-15 years, with permanent dentitions were fabricated. The mesiodistal crown dimensions of teeth were measured with a dial caliper. Tanaka-Johnston method of mixed dentition arch analysis was performed for the study population, and statistical analysis was done. Statistical Analysis Used: Descriptive statistics including the mean, standard deviation, range, and standard error were calculated and tabulated. Results: Tanaka-Johnston's equation when applied to the data available for Mumbai school children, it was observed that it slightly overestimates the tooth size. Conclusions: (1) There was a positive correlation between the width of mandibular incisors and mandibular and maxillary canines and premolars. (2) The Tanaka-Johnston prediction method was not accurate for a sample of Mumbai school children.